And, I mean every word of it: Comments on Francis Dupuis-Déri’s “Global Protesters Versus Global Elite: Are Direct Action and Deliberative Politics Compatible ?” - Genevieve Fuji Johnson (Les Ateliers de l’Ethique, 2012)
Focusing on how recent protests centered on global economic and environmental injustices can contribute to furthering deliberative politics and realizing deliberative democracy, Francis Dupuis-Déri examines the important and historical tension between force and persuasion. However, casting protest as legitimate in the framework of deliberative politics and as serving deliberative democracy obscures its own value in endeavors to achieve social, economic, and environmental justice. Being sympathetic to Dupuis-Déri’s work, I wish to make several, interrelated conceptual and practical clarifications in order to bring back to the fore the fundamental importance of protest, in terms of contributions not to deliberative politics and deliberative democracy but to public discourse.À partir d’une analyse de la manière dont les actions directes s’opposent aux injustices économiques et environnementales et peuvent contribuer à faire avancer et à réaliser la politique délibérative, Francis Dupuis-Déri examine la tension historique et importante entre la force brute et le pouvoir de persuasion. Cependant, le fait de chercher à légitimer la protestation dans le cadre de la politique délibérative et comme un moyen pour les fins d’une démocratie délibérative obscurcit la valeur propre des protestations pour réaliser la justice sociale, économique et environnementale. Étant sympathique aux travaux de Dupuis-Déri, je tiens à faire plusieurs clarifications conceptuelles et pratiques en vue de ramener à l’avant-scène l’importance fondamentale des protestations, en terme de contributions non pas à la démocratie délibérative, mais au discours public.